257. DIFFERENCES IN PERIOPERATIVE STRATEGIES IN ESOPHAGEAL CANCER TREATMENT IN 13 NORDIC UNIVERSITY HOSPITALS CALL FOR HIGH-LEVEL EVIDENCE REGARDING THESE PRACTICES. (24th September 2022) - Achiam, Michael; Nilsson, Magnus; Åkesson, Oscar; Johansson, Jan; Edholm, David; Lindblad, Mats; Szabo, Eva; Sundbom, Magnus; Lindberg, Fredrik; Larsen, Michael Hareskov; Aahlin, Eirik Kjus; Mala, Tom; et al.
Abstract: The Nordic countries have similar health care systems and registries simplifying epidemiological research and the treatment of esophageal cancer is largely centralized. However, differences in treatment traditions can hamper the possibility to assess results and harmonize control arms in joint randomized trials. In setting up a Nordic multi-center randomized trial regarding the use of nasogastric tube (NG-tube) decompression, we aimed to investigate differences in perioperative routines after esophageal resection at Nordic University hospitals. All Nordic University Hospitals with an upper gastrointestinal cancer center (UGC) were contacted regarding a Nordic randomized controlled trial exploring the effects and complications associated with the use of NG-tube after esophagectomy for cancer. Those who chose to join the trial were sent a questionnaire regarding surgical volumes and practices including mean annual number of esophagectomies, surgical method/access, and routine use of pyloric drainage and jejunostomy. In addition, the current standard postoperative use of NG-tube and routine X-ray/CT evaluation, along with postoperative traditions regarding the start of liquid diet was enquired. High volume centers were defined as performing >20 procedures/year. Thirteen of 17 centers with a combined catchment area of 16 million inhabitants and an annual volume of 445 esophagectomies joined the trial network. All, but one center used a total minimally invasive- or hybrid surgical approach but otherwise, the routine use of pyloric drainage and jejunostomy varied widely without being statistically different. All 13 centers reported routine use of NG-tube and 4 employed continuous suction. The NG-tube was removed between 3 and 7 days postoperatively, but also strategies between the centers (suction on NG-tube, start of liquid diet, routine X-ray/CT evaluation) varied without being statistically significant Firm adherence to standardized operations and safety protocols are implemented in Nordic UGCs to reduce the potential consequences of complications. However, the results find the differences in perioperative care after esophagectomy apparent, highlighting the need for high-level evidence regarding these practices. A unified approach may facilitate clinical trial initiatives. There is a paucity of evidence regarding optimal NG-tube use after esophagectomy for cancer and a randomized trial (kiNETiC ISRCTN39935085) investigating this issue is underway.